Stakeholder Engagement in Corporate Community Investment: The Case of Guinness Cameroon - Bamuh, MK (2009)
Corporate community investment has become an important part of business strategy with company executives claiming that local communities are benefiting from their presence. However, how they balance business goals and stakeholder expectations in the process is not properly understood. Since stakeholder engagement is critical in effectively ensuring that the most important social needs are identified and properly executed, this study seeks to develop and test a model of stakeholder engagement in corporate community investment. The aim is to provide practitioners and academicians with practical guidance and tools. Using the stakeholder theory as the bases of the framework, an investigation is made on the nature of stakeholder engagement in Guinness Cameroon in view of obtaining empirical evidence. The main source of primary data is through interviews with company officials and corporate responsibility personnel as well as representatives of key stakeholder groups that have participated in the company’s community investment engagement process. A number of important findings have emerged. First, Guinness Cameroon engages different stakeholders at various stages of corporate community investment projects based on their stake as well as contribution and expertise in realising successful project outcomes. Another key conclusion after testing the model is that the purpose, choice and intensity of engagement with various stakeholders, and the engagement strategies determine the extent to which company and community expectations are met. Lastly, stakeholder engagement has been instrumental in solving problems related to prioritising corporate community investment projects while enhancing transparency and trust. Recommendations on how the company could effectively balance business goals and expectation on the one hand and community needs and expectations on the other are made. The study equally elaborates on directions for future research. Key words: Corporate community investment, corporate community projects, stakeholder engagement, stakeholders.